The testing of photochemical compounds, antioxidant activities, and antibacterial activities of “Sambel Matah” composition from Bali - Ni Made Ayu Suardani Singapurwa; Ida Bagus Wayan Gunam; Pavalee Chompoorat Tridtitanakiat; Ni Made Defy Janurianti; I Made Griya Adi Parta; Putu Diah Wahyuni (Hasanuddin University Food Science and Technology Study Program, 2023)
Sambel matah is a traditional Balinese spice that can be found throughout in Bali. The constituent ingredients of sambel matah, such as onions, limes, lemongrass, and kaffir lime leaves. Sambel matah is served fresh without any heating process. This study aimed to test the content of phytochemical compounds, antibacterial activity and antioxidant in the onions, limes, lemongrass, and kaffir lime leaves. The results were then compared with the extracts of red onion, limes, lemongrass, and kaffir lime leaves. The bacteria used in this study were Salmonnela typhimurium and Escherichia coli. Antibacterial activity was tested by disc diffusion method (KirbyBauer Test). The result of the research, onions, kaffir lime leaves, limes, and lemongrass contain flavonoid compounds, tannins, and phenols in both slurry and ethanol extract. The ethanolic extracts of red onion, limes, kaffir lime leaves, and lemongrass are classified as strong antioxidants. The ethanolic extracts of red onion, limes, kaffir lime leaves, and lemongrass have antibacterial properties against S. typhimurium and E. coli bacteria. Meanwhile, in fresh material (slurry), only limes have antibacterial activity against S. typhimurium and E. coli bacteria with inhibition zone diameters of 14.58±0.767 mm and 8.30±0.483 mm, respectively. Thus, the components of onions, limes, kaffir lime leaves, and lemongrass in sambel matah can inhibit the growth of bacteria, so that the sambel matah becomes more durable even though it is processed without going through the heating process.